Trust across borders - Zaheer, Srilata; Zaheer, Akbar (Journal of International Business Studies, 2006)
We make the case for fresh approaches to examine the role of trust in international collaborations, based on the idea that not only do the levels of trust differ across international borders but also both the nature of trust and the institutional and cultural support for trust can vary across different national contexts. Collaboration partners from different countries are therefore likely to bring either symmetric or asymmetric conceptions of trust to the business relationship. We develop a model and propositions linking symmetry and asymmetry in the institutional and cultural support for trust in international collaborations with the degree of partner interdependence, and identify implications for governance and trust-building investments. We conclude with some suggestions for research that incorporates trust asymmetries between partners.